Navigating Work and Life Boundaries Insights for Distributed Knowledge Professionals - Sarker, Saonee; Ahuja, Manju; Sarker, Suprateek; Bullock, Kirsten M. (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
XIII, 202 p. 5 illus., 3 illus. in color.